Aksi Bina Kesehatan Reproduksi dengan Potensi Tanaman Obat Keluarga di Kelurahan Way Dadi, Bandar Lampung - Sitanggang, Fajar Islam; Riana, Elisa Nurma; Wijayanti, Hendry; Suryanti, Erma (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2023)
Reproductive health is one of the knowledge that is still taboo in society. In fact, it is very important for reproductive development. In adolescents, physical, mental, and social changes must be balanced with good and correct knowledge. Thus, a healthy and quality generation can be created. Way Dadi Village, is one of the villages located in Sukarame District, Bandar Lampung City with a fairly high number of teenagers and adults. This Community Service (PKM) aims to provide knowledge to the public about the importance of reproductive health in maintaining the quality of generations and provide knowledge about the importance of knowing the potential of Medicinal Plants (TOGA) which can be used as prevention of reproductive diseases. This PKM is carried out with a face-to-face method in accordance with health protocols. The PKM method is carried out by evaluating the pre-instruction and post-instruction research questionnaires. Filling in is based on the weighting of understanding starting from not, enough, moderate, good, and very good. Thus, the final post-exam results are obtained with a very good average understanding of up to 86%.